Emotional intelligence and academic performance in first and final year medical students: a cross-sectional study - Chew, Boon How; Md. Zain, Azhar; Hassan, Faezah (BioMed Central, 2013)
Background Research on emotional intelligence (EI) suggests that it is associated with more pro-social behavior, better academic performance and improved empathy towards patients. In medical education and clinical practice, EI has been related to higher academic achievement and improved doctor-patient relationships. This study examined the effect of EI on academic performance in first- and final-year medical students in Malaysia.